A method for accurate zero calibration of asymmetric jaws in single‐isocenter half‐beam techniques. Issue 2 (10th January 2013) - Hernandez, V.; Sempau, J.; Abella, R.; Lopez, M.; Perez, M.; Artigues, M.; Arenas, M.
Abstract : Purpose: : To present a practical method for calibrating the zero position of asymmetric jaws that provides higher accuracy at the central axis and improves dose homogeneity in the abutting region of half‐beams. Methods: : Junction doses were measured for each asymmetric jaw using the double‐exposure technique and electronic portal imaging devices. The junction dose was determined as a function of jaw position. The shift in the zero jaw position (or in its corresponding potentiometer readout) required to correct for the measured junction dose could thus be obtained. The jaw calibration was then modified to introduce the calculated shift and therefore achieve an accurate zero position in order to provide a relative junction dose that was as close to zero as possible. Results: : All the asymmetric jaws from four medical linear accelerators were calibrated with the new calibration procedure. Measured relative junction doses at gantry 0° were reduced from a maximum of ±40% to a maximum of ±8% for all the jaws in the four considered accelerators. These results were valid for 6 MV and 18 MV photon beams and for any combination of asymmetric jaws set to zero. The calibration was stable over a long period of time; therefore, the need for recalibrating is seldom necessary. Conclusions: : Accurate calibration of the zero position of the jaws is feasible in current medical linear accelerators. The proposed procedure is fast and it improves dose homogeneity at the junction of half‐beams, thus, allowing a more accurate and safer use of these techniques.